Um sistema computadorizado para fornecimento de informações contábil-financeiras sobre empresas brasileiras - Silveira, José Augusto Giesbrecht da (1982)
This MBA dissertation develops in its basic features ,a telex-accessed data-base, intended to supply, on a fee basis, financiaI and accounting information on ten thousand of the largest Brazilian enterprises. The áuthor believes that the system is technically and economically feasible, and that it provides some adequate data on which to base the commercial credit decision. The dissertation also covers the best known credit-information agencies, the most important business-ranking publications and two well-established telex-accessed information services in Brazil.